Cephalexin-mediated synthesis of quasi-spherical and anisotropic gold nanoparticles and their in situ capping by the antibiotic - Jagannathan, Ramya; Poddar, Pankaj; Prabhune, Asmita (Journal of Physical Chemistry C, 2007)
Here we report, for the first time, synthesis of gold nanostructures in aqueous medium by reducing gold ions using cephalexin, a potent broad-spectrum antibiotic, where the morphology of the gold nanoparticles is found to be dependent on the concentration of chloroauric acid. The characterization techniques indicate that particle surfaces are coated with the robust layer of the antibiotic making them stable for a long time. Thus, cephalexin acts as both the reducing and the capping agent. NMR and XPS analysis indicate that the sulfur moiety is responsible for the reduction and binding process.

Challenges associated with metal chelation therapy in alzheimer's disease - Hegde, Muralidhar L.; Bharathi, P.; Suram, Anitha; Venugopal, Chitra; Jagannathan, Ramya; Poddar, Pankaj; Srinivas, Pullabhatla; Sambamurti, Kumar; Rao, Kosagisharaf Jagannatha; Scancar, Janez; Messori, Luigi; Zecca, Luigi; et al. (Journal of Alzheimers Disease, 2009)
A close association between brain metal dishomeostasis and the onset and/or progression of Alzheimer's disease ( AD) has been clearly established in a number of studies, although the underlying biochemical mechanisms remain obscure. This observation renders chelation therapy an attractive pharmacological option for the treatment of this disease. However, a number of requirements must be fulfilled in order to adapt chelation therapy to AD so that the term ``metal targeted strategies'' seems now more appropriate. Indeed, brain metal redistribution rather than brain metal scavenging and removal is the major goal of this type of intervention. The most recent developments in metal targeted strategies for AD will be discussed using, as useful examples, clioquinol, curcumin, and epigallocatechin, and the future perspectives will also be outlined.
Keywords: Alzheimer's disease; clioquinol; cuprizone; metal dishomeostasis; metal ions; nanomedicine; Parkinson's disease; polyphenols